Andaliman (Zanthoxylum Acanthopodium DC.), a Rare Endemic Plant from North Sumatra that Rich in Essential Oils and Potentially as Antioxidant and Antibacterial - Nommensen Pangihutan Ompusunggu; Wahyu Irawati (Jurnal Biologi Tropis, 2021)
Andaliman (Zanthoxylum acanthopodium DC.) is one of the endemic plants originating from North Sumatra. This plant is known for its benefits as a special seasoning spice in Batak tribe community. Humans as the image of God are given the ability to conduct an investigation and development of what God has created so that science begins to develop to investigate the potential of andaliman plants in the field of health. This writing aims to determine: 1) morphological and physiological characteristics of andaliman, 2) habitat of andaliman, and 3) utilization of andaliman as antioxidant and antibacterial agent. The method of writing used in the preparation of this article is the study of literature. The results of the literature study show that the andaliman plant has a tap root, woody stems, green, odd-numbered and jagged-edged compound leaves, pale yellow flowers, pepper-shaped fruits, and shiny black or wrinkled black seeds with thick and hard seed shells. Andaliman habitat is a place with an altitude of 1200-1500 masl with an average temperature of 15-18 ÃÅ  C and rainfall of 800-1000 mm/year and soil pH 5.5-7.6. Andaliman fruit contains 29 components of essential oils such as geranyl, cytronella, ÃÂ²-cytronelol, and nerol which have antioxidant activity. Andaliman fruit extract also has antibacterial activity, which inhibits the growth of microbes such as Escherichia coli, Salmonella typhimurium, Bacillus cereus, Pseudomonas fluorescens, Aspergillus flavus, Propionibacterium acnes and Staphylococcus aureus.